Contact angle of Iron Ore Fines: Measurement and Analysis - Huang, Xiaobo; Lv, Xuewei; Bai, Chenguang; Zhang, Rende; Zhou, Maojun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The relative contact angle (θRCA) for seven iron ore fines was measured by using Washburn Osmotic Pressure method under laboratory conditions. By choosing cyclohexane as the reference liquid that can perfectly wet the surface of iron ores and using water as the testing liquid, the relative contact angles for the seven iron ores were measured and varied from 55° to 73°. Some physicochemical properties showed a great influence on relative contact angle. In this paper, the curve of the cosine of θRCA (cos(θRCA)) versus the weight ratio of Fe2O3H/LOI (hematite/loss on ignition) was fitted to an empirical exponential equation with Radj2 larger than 0.92. The measured relative contact angles were found to be in good agreement (Radj2 >0.97) with the calculated contact angles based on the research from Simon M. Iveson, et al. (2004). Besides, an increase in surface morphology index (SMI) and pore volume improved the wettability of the iron ores. Wettability has a great influence on granule strength and the amount of water absorbed, the granulation of a sinter mixture can be enhanced by modifying the mentioned physicochemical properties. The modification of physicochemical properties on iron ores would be another topic in the further study on granulation.